2016
DOI: 10.1083/jcb.201601063
|View full text |Cite
|
Sign up to set email alerts
|

Cancer-associated mutations in the protrusion-targeting region of p190RhoGAP impact tumor cell migration

Abstract: p190RhoGAP (p190A) is a negative regulator of RhoA and localizes to membrane protrusions, where its GAP activity is required for directional migration. Here, Binamé et al. identify the protrusion-localization sequence in p190A and show that cancer-associated mutations in this region affect p190A localization and function as well as tumor cell migration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
47
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 26 publications
(50 citation statements)
references
References 60 publications
3
47
0
Order By: Relevance
“…This binding is mediated by a region of p190ARhoGAP termed the polarization localization sequence, which appears to have an autoinhibitory effect on p190ARhoGAP function. The mechanism through which this autoinhibition is overcome is unclear but, intriguingly, cancer-associated mutations in this region were shown to affect p190ARhoGAP activity and localization, and to impair the directionality of migrating cells ( Binamé et al, 2016 ). Binding of the Rho GTPases RND3 and RAC1 to a similar region has also been implicated in the regulation of the related RhoGAP ARHGAP5 (p190BRhoGAP; Wennerberg et al, 2003 ; Bustos et al, 2008 ).…”
Section: Gap Complexesmentioning
confidence: 99%
“…This binding is mediated by a region of p190ARhoGAP termed the polarization localization sequence, which appears to have an autoinhibitory effect on p190ARhoGAP function. The mechanism through which this autoinhibition is overcome is unclear but, intriguingly, cancer-associated mutations in this region were shown to affect p190ARhoGAP activity and localization, and to impair the directionality of migrating cells ( Binamé et al, 2016 ). Binding of the Rho GTPases RND3 and RAC1 to a similar region has also been implicated in the regulation of the related RhoGAP ARHGAP5 (p190BRhoGAP; Wennerberg et al, 2003 ; Bustos et al, 2008 ).…”
Section: Gap Complexesmentioning
confidence: 99%
“…Hence, there is good rationale for suspecting a role for p190A in invasion and metastasis. However, opposing conclusions have been reached in studies examining how p190A modulates motile capacities of oncogenically transformed cells [ 29 32 ]. It is well-established that p190A is essential for cell polarity and directional migration [ 11 , 33 ], but it remains to be shown if perturbation of these functions confers advantages in the context of cancer.…”
Section: Introductionmentioning
confidence: 99%
“…This raises the exciting possibility that pG1–pG2 is important for full p190RhoGAP activity. This observation may be due to biological effects such as differences in p190RhoGAP localization, as it has recently been suggested that regions near pG1–pG2 drive p190RhoGAP localization to membrane protrusions 11 . Additionally, reported binding partners of p190RhoGAP such as Rnd3 may bind the pG1–pG2 region and affect p190RhoGAP activity 12 .…”
Section: Resultsmentioning
confidence: 99%